(untitled) (Islamic Sciences Journal, 2023)
ABSTRACT Allah, Glory be to Him, has created man and bestowed upon him many great blessings and good and beautiful attributes. Among these great blessings that Allah bestowed on man is the blessing of eloquence and the ability to communicate and speak, as through it man is able to express his feelings and feelings with others. He becames able to understand and deal with other people with ease, and without the blessing of the ability to speak, man would be unable to communicate with the rest people. To thank Allah, a man should utilize his ability to clarify things and to communicate in terms of. Sharia commands concerning using good and approval speachs and stays a way from any speech that may be a cause of conflict or incitement to strife among people.